Simulation of Oil Spill Propagation in the Bach Dang - Lach Huyen Estuary, Hai Phong City - Quoc Trinh, Nguyen; Quang Vinh, Nguyen; Anh Tu, Tran; Thi Thu Ha, Do; Van Hien, Dao (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2S, 2025)
The Bach Dang - Lach Huyen estuarine area in Hai Phong City is a critical maritime gateway for northern Vietnam, hosting dense shipping activities and industrial development. This study applies a hydrodynamic modeling approach to simulate oil spill under varying tidal, wind, and hydrological conditions. Using a combination of numerical models for hydrodynamics and Lagrangian particle tracking, the spatial-temporal behavior of oil slicks was analyzed for selected spill scenarios. The results reveal that tidal currents and seasonal monsoon patterns strongly influence the oil spill trajectory and propagation extent, with high-risk areas identified along maritime navigation channels (from the estuary to the inland) and coastal areas (extending towards Do Son in winter and along Cat Ba Island in summer). The findings provide a scientific basis for oil spill contingency planning, risk assessment, and environmental management strategies in the region.